2021
DOI: 10.1039/d0ma00978d
|View full text |Cite
|
Sign up to set email alerts
|

Bright aspects of defects and dark traits of dopants in the photoluminescence of Er2X2O7:Eu3+ (X = Ti and Zr) pyrochlore: an insight using EXAFS, positron annihilation and DFT

Abstract: Understanding the materials intricacies and fundamental processes involved in dopant and defect luminescence is of paramount importance for design scientists and engineers working towards solid state lighting, optoelectronics, scintillators etc....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…PALSs are reported earlier in similar systems. Gregg et al reported a single positron lifetime of 211 ps in Gd 2 Zr 2 O 7 , while two lifetimes were observed in Nd 2 Zr 2 O 7 annealed at different temperatures as well as in Er 2 Zr 2 O 7 and Er 2 Ti 2 O 7 . Gumber et al also have reported two positron lifetime components with their weighted average as 218 ps in Y 2 Ti 2 O 7 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…PALSs are reported earlier in similar systems. Gregg et al reported a single positron lifetime of 211 ps in Gd 2 Zr 2 O 7 , while two lifetimes were observed in Nd 2 Zr 2 O 7 annealed at different temperatures as well as in Er 2 Zr 2 O 7 and Er 2 Ti 2 O 7 . Gumber et al also have reported two positron lifetime components with their weighted average as 218 ps in Y 2 Ti 2 O 7 .…”
Section: Resultsmentioning
confidence: 98%
“…Pyrochlore materials are currently seeking great attention among the materials science community for the design of multifunctional materials due to their structural flexibility, high stability for heat and radiation, low thermal conductivity, high ionic conductivity, ability to accommodate large concentration of the dopant ion at both A and B sites, and interesting magnetic and electrical properties. Among different pyrochlores based on distinct A and B sites, Y 2 Zr 2 O 7 (YZO) is highly favorable owing its low phonon energy and relatively higher theoretical transmittance . To add to these, they have higher melting point, high chemical and physical stability, and high near-infrared, heat, and radiation reflectivity and can be explored as new heat insulating materials with low thermal conductivity .…”
Section: Introductionmentioning
confidence: 99%